Effect of sodium chloride adsorption on the surface premelting of ice. Issue 35 (30th August 2022) - Berrens, Margaret L.; Bononi, Fernanda C.; Donadio, Davide
Abstract : We characterise the structure of the quasi-liquid layer at two low-index ice surfaces in the presence of sodium chloride (Na + /Cl − ) ions by molecular dynamics simulations and discuss its effect on crystal growth and surface chemistry on ice. Abstract : We characterise the structural properties of the quasi-liquid layer (QLL) at two low-index ice surfaces in the presence of sodium chloride (Na + /Cl − ) ions by molecular dynamics simulations. We find that the presence of a high surface density of Na + /Cl − pairs changes the surface melting behaviour from step-wise to gradual melting. The ions lead to an overall increase of the thickness and the disorder of the QLL, and to a low-temperature roughening transition of the air–ice interface. The local molecular structure of the QLL is similar to that of liquid water, and the differences between the basal and primary prismatic surface are attenuated by the presence of Na + /Cl − pairs. These changes modify the crystal growth rates of different facets and the solvation environment at the surface of sea-water ice with a potential impact on light scattering and environmental chemical reactions.